Modelling progressive failure of segmental linings in shield tunnels - Zhang, Tianqi; He, Bangguo; Chen, Zhitong; Li, Xun; Zheng, Gang (Journal of Civil Engineering and Management, 2025)
Many engineering accidents in shield tunnels occur because localized failure induces the progressive damage or failure of segmental linings. At present, knowledge of the trigger mechanism for this catastrophe is still very limited. While it is difficult to conduct full-scale tunnel failure tests in actual strata, it is feasible to perform numerical simulations of tunnel failure. However, before simulating tunnel failure, it is important to establish a sophisticated model that considers the damage behaviour of segmental linings. In this paper, based on the concrete damage plasticity model and element deletion technology, a sophisticated model of segmental linings was established. The model was verified by data from current structural loading tests. To improve the calculation efficiency, the model was properly simplified. Then, it was applied to simulate the progressive failure of segmental linings due to localized failure in a shield tunnel considering complex soiltunnel interactions. The numerical analysis showed that concrete was damaged in the segments adjacent to the localized failure zone. Some of the stirrups and erection bars in these segments yielded, while the upper and lower rows of steel bars as well as the bolts connecting the segments had sufficient safety redundancy.